Obras raras como patrimônio histórico-cultural e seu uso como fonte infomacional: um estudo de caso na Biblioteca Fran Paxeco - AIRES, Joanne Karoline da Mata (2017)
Study on the preservation of rare works for the preservation and memory of society, with the general objective of analyzing rare works as historical-cultural patrimony. For this, we sought to understand what rare works are and their relation to historical patrimony; To investigate the preservation and conservation of rare works for its access and usability as an information source, and to analyze the Fran Paxeco Library, the ways of access, preservation and conservation of its rare collection. As a methodological procedure, the bibliographical research was adopted, through literature of the area, in order to identify the criteria for evaluation of rare works, its access to the list of rare books with historical patrimony, as well as documentary research, in which they were used Reports and other documents. With a qualitative approach, a case study was made of the Fran Paxeco Library, with an interview application to the responsible librarian, aiming at the recognition of the Library's space, operation and history. As a result, it was observed that the collection of rare works of the Fran Paxeco Library, considered the third largest number of rare works in Brazil, has been preserved and that there are already initiatives to digitize this collection, in order to facilitate its use as an information source. It is concluded with this research the importance of creating policies and projects for the cultural rescue of collections of rare works as an information source.